Representations of women in Zimbabwean contemporary music - Naidoo, Salachi; Pfukwa, Charles (Routledge, 2021)
This paper examines the images of women as portrayed in Zimbabwean contemporary music. The paper compares these images to those found in Zimbabwean literature. What is evidenced in this research is a trend by singers, both male and female, to present a commercialized image of women that hails beauty above intellect. Although the researchers acknowledge the fluidity of meaning and interpretation, a negritudist perception of the ‘woman’ remains all too apparent in the various representations. Female singers as well are seen to fall into the same conventions which this paper seeks to examine.